(untitled) (Revista Espinhaço, 2025)
Further investigation of deforestation in the south of the Amazon is necessary to understand how the phenomenon is configured in local subsystems. The objective of the present study was to analyze the causes of deforestation in Querência - MT, between 1985 and 2018 and to simulate future scenarios until 2030 based on historical trends and measures of environmental governance. We surveyed the leading local and regional causes of deforestation and analyzed them in two distinct periods for calibration (1985-2005) and validation of the spatial model (2005-2018). Based on the simulation, we proposed four possible scenarios for 2030. The results indicated that in Querência - MT, deforestation was associated with proximity to deforested areas, soil types, and rural settlements. The more excellent forest protection was associated with the presence of indigenous lands. The most current deforestation rate was 5% (2005-2018), and model validation reached 0.57 similarity. The proposed scenarios suggest that deforestation in indigenous lands is unlikely to occur by 2030 due to the observed deforestation rate and spatial pattern. However, the misuse of land, such as the suppression of areas protected by law for conservation, is a matter of concern for the coming years, especially in rural settlements.